2016
DOI: 10.1016/j.dib.2016.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological data of nine patients with chronic mucocutaneous candidiasis disease

Abstract: This paper describes the heterogeneous clinical phenotype of a cohort of nine patients diagnosed with heterozygous mutations in STAT1. We report data of extended immunophenotyping over time and we show lung damage in four patients. The increased phosphorylation of STAT1 in response to IFNγ and IFNα stimulation proves the gain-of-function nature of the defects. The data are supplemental to our original article concurrently published “Clinical heterogeneity of dominant chronic mucocutaneous candidiasis disease: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…JAK1/2 inhibition inhibits STAT1‐mediated intracellular signalling, allowing restoration of STAT3 signalling and development of naïve T‐helper cells into a Th17 phenotype (Weinacht et al., ). Granulocyte colony‐stimulating factor or granulocyte monocyte colony‐stimulating factor may enhance Th17 cell differentiation and recovery from fungal infections (Dotta et al., ). Haematopoietic stem cell transplantation (HSCT) is another treatment option, but due to high rates of treatment‐related morbidity and mortality, it is reserved for the most severe CMC cases.…”
Section: Discussionmentioning
confidence: 99%
“…JAK1/2 inhibition inhibits STAT1‐mediated intracellular signalling, allowing restoration of STAT3 signalling and development of naïve T‐helper cells into a Th17 phenotype (Weinacht et al., ). Granulocyte colony‐stimulating factor or granulocyte monocyte colony‐stimulating factor may enhance Th17 cell differentiation and recovery from fungal infections (Dotta et al., ). Haematopoietic stem cell transplantation (HSCT) is another treatment option, but due to high rates of treatment‐related morbidity and mortality, it is reserved for the most severe CMC cases.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that in-vitro treatment with Ruxolitinib significantly decreased the exaggerated cytokine-induced p-STAT1 response in CD4 + T cells of patient P1, suggesting that this therapeutic modality may be useful in case HSCT is unavailable. In addition, case reports with STAT1 GOF mutations have shown that treatment with either granulocyte-colony stimulating factor or granulocyte monocyte-colony stimulating factor may improve the generation of T H 17 cells and recovery from fungal infections (11). …”
Section: Discussionmentioning
confidence: 99%
“…Some of the patients had been previously screened for other mutations (ie, AIRE or CARD9) to rule out other causes of CMCD. In all patients described herein, we found heterozygous mutations in the coiled-coil or DNA-binding domains of STAT1: L283M in P1 and his mother P2, L351F in P3, L400V in P6, T837A in P8, 21,22 T385M in P4 and P5, 23 and A267V in P7. 4 Clinical data from patients were collected from medical records and are briefly summarized in Table I.…”
Section: Methods Patientsmentioning
confidence: 97%
“…Fungal and bacterial infections were observed in all patients with CMCD, whereas viral infections were observed in patients P3 and P8. 21,22 More detailed information on the Methods used are reported in this article's Online Repository at www.jacionline.org.…”
Section: Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation